Erros de imunização em Goiás: análise das notificações - Barboza, Tânia Cristina (2018)
INTRODUCTION: The use of immunobiological has provided progress in the control and prevention of various diseases. However, the increase in the supply of this product, both in quantity and in its diversity, promoted a greater complexity in the vaccination process, revealing the increase of adverse events following immunization (AEFI), including immunization errors (IE), incidents that are avoidable. OBJECTIVE: To analyse the immunization errors occurred and notified in Goiás. METHODOLOGY: This is a retrospective, analytical cohort study of the notifications on IE sent to the Information System on Post-Vaccination Adverse Events Surveillance (SI-EAPV) from the National Immunization Program SI-PNI between August 2014 and December 2017. Data were analysed in the SPSS program, version 24.0. Descriptive analysis was performed using absolute and relative frequencies. The number of errors associated with a vaccine and the number of doses applied and recorded in the SI-PNI of the vaccine associated to the error were used to calculate the incidence rate of IE. The association between the type of immunobiological used and the incidence rate was verified by means of the ratio of incidence rate (RIR) and the respective p-value, using Fisher's exact test. RESULTS: 501 IE occurred, 426 (90.6%) IE without AEFI and 47 (9.4%) IE with AEFI. The overall incidence rate was 4.05 IE/100.000 doses applied, the most frequent were those related to the prescription and/or indication of the immunobiological (26.9%), the inadequate interval between doses (18.2 %) and the error in the administration technique (14.2%). Most cases occurred during administration of routine doses (92.6%) and a higher proportion of IE were related to vaccines (15.4%), yellow fever (12%), HPV (10%), pentavalent (7.4%) and VORH (7.0%). The majority of IE (416; 80.0%) occurred in municipalities in the interior of the State and in female individuals (313; 62.5%). Regarding the age group, IE in children under five involved more than half of the cases analysed (55.7%). Approximately half (49.7%) of IE occurred on administration of the first dose of immunobiological and 58.1% involved immunobiological administered intramuscularly. Of the total IE with AEFI, 139 events occurred, including local manifestations (66.2%) and systemic manifestations (33.8%). The five most reported AEFI were local pain (14.4%), edema or flushing (12.2%), erythema (12.2%), heat (9.4%) and nodule (5.0%). There was a higher frequency of IE with AEFI related to BCG (23.4%), pentavalent (10.6%), yellow fever (8.5%), and HPV (8.5%) vaccines. CONCLUSION: The study evidenced that errors are occurring in the immunization process, and it is necessary to adopt prevention strategies, focusing on systemic measures and human resources development, improving the quality of service and promoting safe vaccination in vaccine rooms.